The Overview of Anti-PGL-1 and Anti-IDALLE L-ESAT 6 IgG Antibody Titers in Household Contact of Leprosy - Hadi, Moch Irfan; Faizah, Hanik; Alamudi, Muhammad Yusuf (International Conference on Sustainable Health Promotion, 2018)
Household contact is a high-risk group for leprosy transmission. Household contact with a high titer of Glycolipid-1 phenolic possesses a higher risk to develop into leprosy. This study was an observational study. The subject of the study consisted of 95 household contacts living at the house of leprosy patient in Brondong Subdistrict, Lamongan Regency, East Java, Indonesia whom anti-phenolic Glycolipid-1 and anti-IDALLE L-ESAT 6 IgG antibody titers were measured. Measurement of anti-PGL-1 and anti-IDALLE L-ESAT 6 IgG levels used the enzyme linked immunosorbent assay (ELISA) technique. The mean levels of anti-PGL-1 IgG in all subjects were 134.54 units / mL (± 295.15) while the levels of anti-IDALLE L-ESAT 6 IgG were 408.61 units / mL. There was a significant positive relationship between levels of anti-PGL-1 IgG with anti-IDALLE L-ESAT 6 IgG (r = 0.247, p = 0.016) in the household contacts of leprosy patient.